Removal of Chromium (III) Ions from its Aqueous Solution on Adsorbent Surfaces: Charcoal, Attapulgite and Date Palm Leaflet Powder - H Abdulla, Fatma (Iraqi Journal of Science, 2026)
n the present work, a study is carried out to remove chromium (III) fromaqueous solution by: activated charcoal , attapulgite and date palm leaflet powder(pinnae). The effect of various parameters such as contact time, and temperature hasbeen studied. The isotherm equilibrium data were well fitted by Freundlich andLangmuir isotherm models. The adsorption capacity of chromium (III) that wasobserved by activated charcoal , attapulgite and date palm leaflet powder (pinnae)increased with the rise of temperature when the concentrations of Cr (III) were 600,700 and 100mg/L respectively. The greatest adsorption capacity ofactivatedcharcoal , attapulgite and date palm leaflet powder (pinnae) at 10°C was 7.51, 5.39and 0.77mg.gˉ¹ respectively and reaching 9.99, 8.82 and 1.43mg.gˉ¹ at 37.5°C. Thethermodynamics study showed that the chromium (III) ions adsorption isendothermic and spontaneous with the increase of randomness at the solid-solutioninterface that involves adsorption and absorption mechanism.